2001
DOI: 10.1562/0031-8655(2001)0730636amofct2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence Microscopy of Fresh Cervical-Tissue Sections Reveals Alterations in Tissue Biochemistry with Dysplasia¶

Abstract: Fluorescence spectroscopy offers an effective, noninvasive approach to the detection of precancers in multiple organ sites. Clinical studies have demonstrated that fluorescence spectroscopy can provide highly sensitive, specific and cost-effective diagnosis of cervical precancers. However, the underlying biochemical mechanisms responsible for differences in the fluorescence spectra of normal and dysplastic tissue are not fully understood. We designed a study to assess the differences in autofluorescence of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(90 citation statements)
references
References 15 publications
6
80
2
2
Order By: Relevance
“…Collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) are predominant intrinsic tissue molecules that emit fluorescence upon excitation with UV or blue light. 42,63 Alterations in the biochemical composition of tissue during the early stages of carcinogenesis can be observed as a change in the fluorescence signals captured indicating cancer-associated tissue changes. Various wavelengths for both the excitation (300-480 nm) and emission (500-700 nm) of intrinsic fluorophores have been utilized (especially for auto-fluorescence spectroscopy), but typically blue light excitation (~450 nm) is preferred to UV light, due to the low UV transmittance of conventional optics.…”
Section: Auto-fluorescence Imaging (Endogenous Contrast)mentioning
confidence: 99%
“…Collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) are predominant intrinsic tissue molecules that emit fluorescence upon excitation with UV or blue light. 42,63 Alterations in the biochemical composition of tissue during the early stages of carcinogenesis can be observed as a change in the fluorescence signals captured indicating cancer-associated tissue changes. Various wavelengths for both the excitation (300-480 nm) and emission (500-700 nm) of intrinsic fluorophores have been utilized (especially for auto-fluorescence spectroscopy), but typically blue light excitation (~450 nm) is preferred to UV light, due to the low UV transmittance of conventional optics.…”
Section: Auto-fluorescence Imaging (Endogenous Contrast)mentioning
confidence: 99%
“…In fact, during the forming of the epithelial carcinogenesis, the morphological structures of these three layers gradually develop some obvious alterations, such as increase in the keratinizing layer thickness, cellular nuclear enlargement in the epithelial cell layer and variation of collagen framework in the stromal layer [2][3][4][5]. The corresponding autofluorescence spectroscopy of different layers also shows apparent changes [6][7][8][9]. In biology and medicine, the spectroscopic measurement is combined with an optical microscope to generate images with spatially-resolved biochemical functional information, which is known as spectral imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Although these problems can be overcome with the use of fluorescent microscopy, the complication of inherent autofluorescence has to be dealt with. Autofluorescence has been noted in a variety of human and animal tissues and many investigators have suggested that this autofluorescence is inversely correlated with metabolic and proliferative activity, and hence the redox state of the tissue at fixation (Poot et al 1985, Shimazaki et al 1993, Drezek et al 2001. Interestingly, autofluorescence in the human hair follicle has recently been linked with the possible presence of melanocyte and keratinocytes stem cells (Wun et al 2005).…”
Section: Introductionmentioning
confidence: 99%